The Influence of the 2024 Presidential and Vice Presidential Election Socialization Through the Use of Instagram Social Media on Increasing Political Participation of Voters in Sukabumi City - Kustiyawahyudi, Muhammad Rival; H. Suwiryo, Darmo; Rachmawati, Ike (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study examines the influence of social media, specifically Instagram, on political participation in Sukabumi City during the 2024 Presidential Election. With the rise of digital platforms, social media has become a pivotal tool for political information dissemination. The objectives of this research include evaluating the frequency of Instagram usage for political information, assessing voter participation levels, and analyzing the impact of Instagram socialization on political engagement. A quantitative research design was employed, utilizing surveys to gather data from 100 respondents selected from Sukabumi City’s registered voters. The results indicate a significant correlation between Instagram usage for political purposes and increased political participation. Specifically, the regression analysis shows that 30.5% of the variation in political participation can be attributed to Instagram use. This study highlights the role of social media in enhancing voter awareness and engagement, with a 4% increase in voter participation from the 2019 to the 2024 election. The findings underscore Instagram’s effectiveness as a medium for political socialization and its positive impact on voter turnout. These results suggest that social media platforms can play a critical role in promoting democratic engagement, particularly in the context of modern electoral campaigns